Silver nanoparticles coated with metabolites of Pseudomonas sp. N5.12 inhibit bacterial pathogens and fungal phytopathogens - Svitlana Plokhovska; Ana García-Villaraco; Jose Antonio Lucas; Francisco Javier Gutierrez-Mañero; Beatriz Ramos-Solano (Scientific Reports)
Abstract The synthesis of nanomaterials from PGPB is an exciting approach and it’s often used in agriculture as nano-fertilizers and nano-pesticides. The present study reports a new approach to biosynthesis of silver nanoparticles (AgNP), using bacterial metabolites as agents to reduce Ag+, which will remain as coating agents able to prevent microbial growth. Silver NP were biosynthesized using the bacterial metabolites produced by the beneficial strain Pseudomonas sp. N5.12. Optimization of physicochemical parameters (temperature, pH, and AgNO3 concentration) for the synthesis of AgNP was carried out. In each condition, success on AgNP synthesis was determined by UV–Visible spectra showing peaks between 400 and 450 nm. TEM analysis showed that the AgNP are spherical in shape with an average particle size ranging from 13.75 ± 0.47 nm to 20.71 ± 0.43 nm, covered with a unique organic matter corona of bacterial metabolites. The best parameters for AgNP biosynthesis by Pseudomonas sp. N5.12 occurred with 24 h bacterial metabolites, temperature of 37 °C, pH 9 and a ratio of 2:4 (v: v; bacterial supernatant: 1 mM AgNO3). The biosynthesized AgNP inhibited growth of human pathogenic bacteria better than equivalent AgNO3 concentration. Growth of bacterial and fungal phytopathogens was also inhibited with striking effects on Alternaria sp. (74% inhibition) and Stemphylium sp. (52% inhibition), appearing as promising tools to biocontrol fungal diseases in agriculture.